Peranan Wakaf Produktif Pemuda Muhammadiyah Untuk Kesejahteraan Warga Desa Longkeyang, Bodeh, Pemalang - Bakhri, Amirul (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2017)
AbstractOne of the forms of worship to draw closer to Allah SWT related to property is donated. waqf istismari also called productive waqf, waqf property that is used for investment purposes, whether in agriculture, industry, trade, and services. This endowment is growing problems in the village Longkeyang, where the youth of Longkeyang attempted endowment for the welfare of citizens. In 2006, approximately 10 people from the youth of the Longkeyang together activists AMM (Angkatan Muda Muhammadiyah) began a new initiative is to create a new institution that was later (in 2010) was named after the Badan Pekerja Pengembangan Ranting Muhammadiyah (BP2RM). (1) The first step movement endowment productive Muhammadiyah Youth in Longkeyang namely (a) the anxiety of citizens and youth of the organization is stagnant and also go hand in hand some scholars who died, so no worries "if shortly Muhammadiyah in Longkeyang will run out" as the scorn of other people. (B) Establish Badan Pekerja Pengembangan Ranting Muhammadiyah (BP2RM) Longkeyang village. (C) Movement Endowments Endowments coins For Productive. The two (2) Management of communal ownership of productive Youth in Longkeyang namely (a) From the collected coins donated land and then bought 1,500 m maximized as initial capital. (B) The existing endowments worked together to reduce the cost of key crops albasia timber, then the cost of treatment using the results of intercropping banana plants. The third (c) In the future, earning endowment will be managed by the sharing system, since from 2006 to 2010 the endowment of productive trees used for the expansion of land. (3) The Role of Waqf Productive Youth Welfare Citizens For The Longkeyang namely (a) The results of this productive endowments, are not significant, but citizens can already feel as waqf land managers and also from the results of the banana crop intercropping. (B) Some of the programs that have resulted from the productive management of waqf endowments suppl shroud support fund for volunteers who want to stay.Keywords: Endowments, Awqaf Productive, Youth of Muhammadiyah.